Auditor Independence and Threats: Mediating Role of Auditor Ethics - Hamid, Abdul; Soewarno , Noorlailie; Isnalita, Isnalita (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This research aims to examine the mediating role of auditor ethics on the influence of independent auditors on auditor threats. Research Background: Behind the increasing public trust in accountants recently, Independence has come under sharp scrutiny from the public. Method: Research was conducted using a quantitative approach. The survey participants are auditors in Indonesia. The number of respondents was 96 auditors. Results: The results of this study indicate that auditor ethics mediates the influence of Independence on the threats that auditors will face. Apart from that, the results of this research also show that auditor independence has a positive relationship with auditor ethics. Then, auditor ethics have a positive effect on auditor threats. Conclusion: This research provides implications for Auditors at the Indonesian Institute of Public Accountants to increase awareness of threats that arise through their involvement as external auditors. Awareness of the importance of professional ethics to maintain Independence from threats. This research fills the gap in the literature regarding auditor independence and threats by showing that ethics plays a mediating role in avoiding threats that auditors face. This research can enrich the literature on external audit standards, especially the auditor's duties, by prioritizing ethics in attitudes and behavior as an independent and professional auditor.